2011
DOI: 10.1111/j.2042-7158.2011.01339.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel gel formulations with catanionic aggregates enable prolonged drug release and reduced skin permeation

Abstract: No morphological differences could be distinguished between the skin samples exposed to the different formulations or the reference. Skin permeation was compared with silicone sheet permeation and the results indicated that silicone sheets could be used as a model of skin when using these formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…CPDR=k 1 ·t m +k 2 ·t 2m (4) where, CPDR=Cumulative percent drug release, k 1 =Rate of drug diffusion due to Fickian diffusion, k 2 =Rate of drug diffusion due to polymer relaxation, and m=Composite diffusion exponent.…”
Section: -4 Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…CPDR=k 1 ·t m +k 2 ·t 2m (4) where, CPDR=Cumulative percent drug release, k 1 =Rate of drug diffusion due to Fickian diffusion, k 2 =Rate of drug diffusion due to polymer relaxation, and m=Composite diffusion exponent.…”
Section: -4 Mechanical Propertiesmentioning
confidence: 99%
“…It promotes the formation of water-in-oil emulsions. Due to its non-ionic nature, Span 60 is biocompatible and non-irritant [4][5][6]. In addition to its afore-mentioned properties, Span 60 has been tried as a structuring agent for developing formulations for cosmetic, food and pharmaceutical applications [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, two main strategies to improve release properties of catanionic vesicles are employed which are (1) incorporation of vesicles into the gels and (2) preparation of environment sensitive vesicles. Catanionic aggregates formed from drug and oppositely charged surfactant and then incorporated into the gel have been extensively studied by Edsman's group with the objective to utilize them for prolonged release [90][91][92][93][94][95][96]:…”
Section: Pharmaceutical Applications: Drug Delivery Systemsmentioning
confidence: 99%
“…(6) Release profiles of (1) alprenolol/SDS aggregates incorporated into the SoftCAT and Carbopol ® gels [95] and (2) tetracaine/SDS or capric acid aggregates incorporated into the SoftCAT and carbomer gels [96] have shown that prolonged drug release from this system enables prolonged skin penetration.…”
Section: Pharmaceutical Applications: Drug Delivery Systemsmentioning
confidence: 99%
“…The use of catanionic aggregates formed from drug compounds with oppositely-charged surfactants has received particular attention for drug delivery applications [24,25,26,27,28,29,30,31,32,33]. Aggregates made of ionic drugs and surfactants have proven to extend the drug release from synthetic gels from hours to days due to the presence of vesicles or entangled micelles [24,26].…”
Section: Introductionmentioning
confidence: 99%